The measles epidemic trend over the past 30 years in a central district in Shanghai, China. - Jie Gao; Bing Shen; JianJing Xiong; Yihan Lu; Qingwu Jiang (PLoS ONE)
Background Measles vaccination over the past 50 years has greatly reduced the incidence of measles. However, measles among migrants and the resulting changes in epidemiological characteristics have brought new challenges to the elimination of measles. We aim to describe the measles epidemic trend over the past 30 years in a central district in Shanghai, China. Methods The present study was conducted in the Jing'an District, which is located in the center of Shanghai. Based on historical surveillance data of measles, we calculated the incidence of measles among local residents and migrants separately. Next, we classified all of the cases of the measles among local residents between 1984 and 2015 into 8 age groups and 5 birth cohorts. Finally, we calculated the measles incidence in each time period by the different age groups and birth cohorts, to understand the measles epidemic trend over past 30 years in the Jing'an District. Results A total of 103 cases of measles were reported from the Jing'an District, Shanghai, from 1984 to 2015. For infants less than 1 year of age and adults over 30 years of age, the incidence of measles continued to rise over the past 30 years. For a specific birth cohort, the incidence of measles after measles vaccination declined initially, and was then followed by a rebound. Conclusions The incidence of measles in older adults and infants increased in some developed regions, which slows the process of measles elimination. This suggested that the population immunity against measles after measles vaccination would gradually reduce with time. We recommend supplemental immunization against measles in adults in order to reduce the immunity decline, especially for migrants.